Kajian Kualitas Walkability di Koridor Jalur Wisata Kota Yogyakarta: Studi Kasus: Koridor Jalan Panembahan Senopati, Jalan Sultan Agung dan Jalan Kusumanegara - Eigner; Paulus Bawole (ATRIUM: Jurnal Arsitektur, 2022)
Title: Study of Walkability Quality on Tourism Line Corridor of Yogyakarta City Case Study: Corridor line of Panembahan Senopati, Sultan Agung, and Kusumanegara Street   Walkability measures pedestrian paths' connectivity, quality, and friendliness. Walkability allows everyone to gain experiences in the surrounding environment and meet their needs independently. From the tourism side, pedestrian walkability is the primary support for the convenience of tourists. The development of the city of Yogyakarta that supports tourism seeks to increase connecting routes between available tourist destinations. One of the corridors connecting several tourist destinations is the connecting line between the zero point toward the eastern boundary of Yogyakarta City. This corridor connects several exciting tourist destinations, including The National Tourism Strategic Area (KSPN) in the form of the Sultanate Palace, Pakualaman Palace, and a tourism potential known as the "Gembira Loka" Zoo. This study aims to evaluate the quality of pedestrians in the corridors described above. This research is qualitative research using descriptive methods to explain research findings. The evaluation and assessment were carried out using the Global Walkability Index Criteria. The findings stated that the condition of the pedestrian path still had some problems, such as permanent and non-permanent obstacles, narrow lanes, not yet friendly for the disabled, inadequate crossing points/spots, and a lack of convenient support facilities.